Proposed material for beginning reading in Ilokano - Pastores, Segunda A. 1925- (s.n.], 1968)
In an attempt to aid a first grader gain independence in word attack at the earliest time possible, the study proposed a series of beginning reading materials in Ilocano. Twenty lessons corresponding to the twenty letters of the Ilocano alphabet composed the series. Sample tests on word recognition and comprehension are included. Accompanying the beginning reading material is a manual giving instructions on how to carry out the lessons.